2008
DOI: 10.1161/hypertensionaha.107.105577
|View full text |Cite
|
Sign up to set email alerts
|

High-Normal Blood Pressure Is Associated With Poor Cognitive Performance

Abstract: Abstract-While the relation between systolic blood pressure (SBP) and vascular events is linear down to the high-normal range, the relation between SBP and cognition is less clear. We cross-sectionally assessed the relation between SBP and cognition in a cohort extending from mid-to late-life. From a total of 2200 community-dwelling individuals we recruited 377 aged 44 to 82 years (median: 64 years, 171 male) in the SEARCH-Health study (Systematic evaluation and alteration of risk factors for cognitive health)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 46 publications
5
86
2
5
Order By: Relevance
“…Despite significant variability (as reflected by the wide scatter in Figure 1), there was an inverse relationship between BP index and adjusted PIQ score in this study, suggesting that higher systolic and diastolic BP are associated with a lower PIQ score, even in the normotensive range. These results are consistent with a recent study in adults showing that the relation between global cognitive performance and SBP was linear, even in the normotensive range, with the best cognitive performance in subjects with SBP Ͻ120 mmHg (15).…”
Section: Discussionsupporting
confidence: 93%
“…Despite significant variability (as reflected by the wide scatter in Figure 1), there was an inverse relationship between BP index and adjusted PIQ score in this study, suggesting that higher systolic and diastolic BP are associated with a lower PIQ score, even in the normotensive range. These results are consistent with a recent study in adults showing that the relation between global cognitive performance and SBP was linear, even in the normotensive range, with the best cognitive performance in subjects with SBP Ͻ120 mmHg (15).…”
Section: Discussionsupporting
confidence: 93%
“…Participants were asked to learn as many words as possible out of a list of 15 words. As primary outcome measure ''memory score,'' we considered the total number of retrieved words after 30 min (delayed memory), adjusted for false positive misidentifications (86,87), in line with previous studies (36,37,88), and with signal detection theory (89). Additionally, analysis was conducted for total number of retrieved words without adjustment for false-positives, and for total numbers of false-positive errors.…”
Section: Methodsmentioning
confidence: 99%
“…An American Heart Association statement recommends blood pressure control in patients poststroke (Class I, B) and also treatment in the younger of the elderly (Class IIa, B) [3]. A study reported a progressive cognitive decline for values of systolic BP between 120-140 mm Hg [25], suggesting need for treatment at prehypertensive levels. Calcium-channel blockers and inhibitors of renin-angiotensinaldosterone system (RAAS) increase Aβ removal from the brain and protect against cognitive impairment in animal models [26,27].…”
Section: Prevention Of Stroke and Dementia By Htn Treatmentmentioning
confidence: 99%